Dinosaur adventures - Bromage, Fran (Essex, England Miles Kelly Publishing, 2018)
This fantastic compendium of dinosaur tales includes four original fiction stories featuring a noisy T rex, a clumsy Ankylosaurus, a speedy Velociraptor and a ditzy Diplodocus. The large format allows the stunning full-bled artwork scenes to jump off the page, helping to engage and enthrall younger children as they delve into each story
T rex : The big scare -- Diplodocus : The dippy idea -- Velociraptor : The speedy tale -- Ankylosaurus : The clumsy club
English stories
1
Keywords: Dinosaurs -- Juvenile fiction; Emotions -- Juvenile fiction; Friendship -- Juvenile fiction